Etyka w sprzedaży produktów finansowych - Sałek, Przemysław (Annales. Etyka w Życiu Gospodarczym, 2015)
The author examines the existence of unethical behaviour of the employees of financialinstitutions. This paper is based on studies carried out with the aid of the ‘mysteryshopper’ method in Warsaw. Based on the survey, the author wanted to checkwhether a client is well informed about the real costs of credit and whether a clientis asked for an opinion about credit insurance. The outcomes have been comparedwith the findings of Robert Rogowski published in ʿThe moral dimension of theeconomic crisis’.